Harnessing WebGL and WebSockets for a Web-Based Collaborative Graph Exploration Tool - Zimmer, Björn; Kerren, Andreas (Engineering the Web in the Big Data Era, 2015)
The advancements of web technologies in recent years made it possible to switch from traditional desktop software to online solutions. Today, people naturally use web applications to work together on documents, spreadsheets, or blogs in real time. Also interactive data visualizations are more and more shared in the web. They are thus easily accessible, and it is possible to collaboratively discuss and explore complex data sets. A still open problem in collaborative information visualization is the online exploration of node-link diagrams of graphs (or networks) in fields such as social sciences or systems biology. In this paper, we address challenges related to this research problem and present a client/server-based visualization system for the collaborative exploration of graphs. Our approach uses WebGL to render large graphs in a web application and provides tools to coordinate the analysis process of multiple users in synchronous as well as asynchronous sessions.